Social and Economic Mapping Sisi Madura dan Sisi Surabaya dalam Mendukung Tata Ruang Suramadu - Hakim, M. Andri (Jurnal Sosial Ekonomi Pekerjaan Umum, 2009)
The view of the Madura as the isolated area and low investment attractiveness, to be turned toward the post-development of Suramadu Bridge. Madura become potential and suitable investment area. Therefore, land use on the side of Surabaya and Madura must be controlled or defined as "high control zone". The development of a less controlled area, in the long run will cause many problems. This research is aimed to provide an overview of the socio-economic aspects of cultural aspects of Madura Island and City of Surabaya is expected to affect the compliation of spatial Suramadu.This research uses descriptive method with qualitative approaches. The sustainable aspects that may affect the optimum use of Suramadu Bridge has been identified and the short term program has also formulated. The seven aspects representing sustainable development of Suramadu Bridge among other the spatial planning status, access and transportation, migration of population, impact of new technology, production and market, socio culture, public services, administration and institutional.It is recomended that this research finding could be the important input of Social and Economic factor for the preparation of BPPWS Master Plan and Suramadu Spacial Planning.